Controlled Release Fertilizer Encapsulated by Glutaraldehyde-Crosslinked Chitosan Using Freeze-Drying Method - Adhitasari Suratman; Dwi Ratih Purwaningsih; Eko Sri Kunarti; Agus Kuncaka (Indonesian Journal of Chemistry, 2020)
A new encapsulation of NPK fertilizer hydrogel granules made from glutaraldehyde crosslinked chitosan has been successfully fabricated. This designed fertilizer was aimed to maximize the fertilizing process in the soil, as the environmental pollution affected by the excess release of the nutrients can be prevented. The granule was prepared from biodegradable chitosan crosslinked with glutaraldehyde by applying a method of air and freeze-drying. The release test proved that this designed fertilizer showed a good performance as a Controlled Release Fertilizer (CRF) in which the hydrogel granules could absorb and deposit large amounts of NPK. Later on, they could also release large amounts of NPK as well, unlike several types of CRFs. The release percentage of NPK out of the granules tended to decrease with an increase of pH at a range close to the average pH of the soil, which is neutral to base. Comparing two methods, the freeze-drying technique, which yields a bigger pore size, showed a higher release percentage than air-drying. The release kinetics of the granules followed the Korsmeyer-Peppas model.